Biosynthesis of tasikamides via pathway coupling and diazonium-mediated hydrazone formation - Ma, Guang-Lei (2022)
Naturally occurring hydrazones are rare despite the ubiquitous usage of synthetic hydrazones in the preparation of organic compounds and functional materials. In this study, we discovered a family of novel microbial metabolites (tasikamides) that share a unique cyclic pentapeptide scaffold. Surprisingly, tasikamides A−C (1−3) contain a hydrazone group (CNN) that joins the cyclic peptide scaffold to an alkyl 5-hydroxylanthranilate (AHA) moiety. We discovered that the biosynthesis of 1−3 requires two discrete gene clusters, with one encoding a nonribosomal peptide synthetase (NRPS) pathway for assembling the cyclic peptide scaffold and another encoding the AHA-synthesizing pathway. The AHA gene cluster encodes three ancillary enzymes that catalyze the diazotization of AHA to yield an aryl diazonium species (diazo-AHA). The electrophilic diazo-AHA undergoes nonenzymatic Japp−Klingemann coupling with a β-keto aldehyde-containing cyclic peptide precursor to furnish the hydrazone group and yield 1− 3. The studies together unraveled a novel mechanism whereby specialized metabolites are formed by the coupling of two biosynthetic pathways via an unprecedented in vivo Japp−Klingemann reaction. The findings raise the prospect of exploiting the arylamine-diazotizing enzymes (AAD) for the in vivo synthesis of aryl compounds and modification of biological macromolecules.